THE MAIN ROLE OF SOCIO-ECONOMIC PROGRAMS IN THE AGRICULTURAL SECTOR DEVELOPMENT OF CHINA - Madiev, Д A (Journal of Oriental Studies, 2016)
This article is made versatile analysis of the effectiveness of reforms in the agricultural development of China. There have been improvements and advances in the management of agriculture and increasing the types and volume of production. Сonsidered the seven direction of development of agriculture, taken by the All-Chinese Council for Agriculture.